Navigating the Path to Equitable and Sustainable Digital Agriculture among Small Farmers in Malaysia: A Comprehensive Review - Omar Abu Hassim; Ismah Osman; Asmah Awal; Fhaisol Mat Amin (Information Management and Business Review, 2024)
The agriculture sector has transformed with the advent of digital agriculture, smart farming and Agriculture 4.0, yet the social science aspects remain underexplored. This article aims to address this gap by conducting a comprehensive review of 17 studies that focus on the social, economic, and institutional dimensions of precision farming, digital agriculture, smart farming and Agriculture 4.0. The objectives are to explore the dynamics between digital agriculture and farm diversity and to identify emerging concerns related to economics, business, institutions, and ethics. Methodologically, the review synthesizes existing literature on socio-cyber-physical-ecological systems, digital agriculture policy processes, the transition from analog to digital agriculture and the global landscape of digital agriculture development. It adopts a multidisciplinary and transdisciplinary approach to provide a holistic understanding of the topic. The outcomes reveal significant implications for policymakers, farmers, and stakeholders in the agriculture sector. Key findings highlight the necessity of addressing social and economic impacts, such as data privacy, security, and accessibility, and the effects of automation on rural employment and community structures. The review emphasizes the importance of developing institutional and governance frameworks to support digital agriculture practices and tailoring policies to promote sustainable and equitable use of digital technologies. It explores how infrastructure, connectivity and local capacities influence the adoption of digital agriculture technologies. The review advocates for further research on the intersection of digital agriculture with broader societal trends, such as climate change, urbanization, and food system transformations, to develop strategies for sustainable and resilient food systems.